CLINICO PATHOLOGICAL CHARACTERISTICS AND TREATMENT OUTCOME IN FEMALE PATIENTS WITH CARCINOMA TONGUE - Jones, Joneetha; Suresh, Akhil P; V, Vinin N; M, Geetha; Yahiya, Nabeel; Bindu , Anilkumar; Rejeesh, jyothi (International Journal of Pharma and Bio Sciences, 2026)
Globally, oral cancer is the sixth most common cancer. In India it is the most common cancer in men and third most common cancer in women, the tongue is the most common location and accounts for approximately 25% to 40% of oral cancers. The incidence of carcinoma tongue is higher in an older age group, especially men, with a long history of tobacco use and alcohol consumption. Recently, however, there has been an increase in the incidence of oral cancer in a younger population especially in women who have not been exposed to the conventional risk factors. Although tongue cancer is not one of the most common cancers in women, this increase in occurrence has raised concern. This study intends to find out the patterns of presentation and treatment outcome in female patients who were diagnosed with carcinoma tongue at our center. This was a retrospective analysis to describe the clinic pathological characteristics and to find out the treatment outcome in female patients with carcinoma tongue treated at our center during the period 1st January 2015 to 31st December 2020. All cases of histopathologically proven tongue cancers were included in our study. The quantitative variables were summarized using descriptive statistics and the qualitative variables were summarized using number and percentages. The Kaplan- Meier method was used to find out the overall and disease free survival. The data was analyzed using statistical software SPSS version 20. A total of 295 females were diagnosed with carcinoma tongue during the study period. The median age of the study population was 62 years.45% patients had a history of chewing tobacco.25%patients had family history of malignancy. 43% of patients had comorbidities. The most common site of involvement was the lateral border in 82% of cases.42% had well differentiated squamous cell carcinoma histology.71% of patients presented with ulcer and pain.62 % of patients presented with stage III and stageIV disease. 52% patients underwent radical intent treatment.21% patients underwent palliative intent radiation or chemotherapy treatment and 27% patients did not undergo any treatment. Median follow up was 36.9 months. The three year DFS was 71% and 3-year OS was 76.5%. The 3 year DFS and OS for stage I disease was 80.3% and 80.5%. For stage II it was 88.7% and 95.8%. For stage III it was 69.2% and 69.8% and for stage IV it was 54.6% and 62.6% respectively. Oral tongue cancer presents in advanced stages and carries poor prognosis. Its increasing incidence in females is a growing concern. Our study showed that the clinicopathological profile and outcomes were similar to the literature data. More studies are needed to find out if there is any difference in treatment outcome with the male counterparts. Also studies are needed to find out the mechanisms involved in carcinoma development in non-habituate females.